Indeed, space matters in processes of subjectivation. (August 2020) - Miggelbrink, Judith
Abstract: The commentary focuses on the role of space and spatio-historic contexts in processes of subjectivation highlighted in Bernd Belina's plenary lecture. While applauding to his general argument, the commentary argues for diving deeper into the question how neoliberalism including neoliberal subject formation has been implemented through certain places and practices that aim at positioning subjects in a specific way, e.g. through youth and educational institutions or health and pension policies. It pleas for taking up again Doreen Massey's progressive sense of place.